(untitled) (Konferensiyalar | Conferences, 2024)
While teaching any foreign language in any type of education system there appears a necessity to evaluate students’ language skills for various purposes as to identify language level for choosing appropriate teaching materials, to check the level of material perception by the students etc. Therefore, assessment is the system of collection and evaluation of certain information to improve students’ knowledge and to choose appropriate teaching method. Literate assessment and application of correct testing system helps not only teachers to identify the point where students have stopped but also make students learn while fulfilling various quizzes.